Предмет: Алгебра,
автор: lifeminelivegood
Упростите выражение (а+3) в квадрате -2а(3-4а) и найдите его значение при а=-1 третья
Ответы
Автор ответа:
0
=а²+6а+9-6а+8а²=9а²+9=9(а²+1)=9*(-1/3²+1)=9*(1/9+1)=9*1 1/9=9*10/9=10
Автор ответа:
0
(а+3)²+(а+3)×(а+3)=а²+6а+9
-2а(3-4а)=-6а+8а²
Подставляем:
а²+6а+9-6а+8а²=9+9а²
при а=-1
9+9а²
1)9а²=9×1²=9×1=9
2)9+9=18
Похожие вопросы
Предмет: Русский язык,
автор: S239
Предмет: География,
автор: ivankomisar29
Предмет: Английский язык,
автор: archimami28
Предмет: История,
автор: ДашаПошечко2004
Предмет: Обществознание,
автор: kilkaM827AA